2003
DOI: 10.1590/s0004-282x2003000600010
|View full text |Cite
|
Sign up to set email alerts
|

Corpora amylacea in temporal lobe epilepsy associated with hippocampal sclerosis

Abstract: -Hippocampal sclerosis (HS) is the commonest pathology in epileptic patients undergoing temporal lobe epilepsy surgery. Beside, there are an increased density of corpora amylacea (CA) founded in 6 to 63% of those cases. Objective: verify the presence of CA and the clinical correlates of their occurrence in a consective series of patients undergoing temporal surgery with diagnosis of HS. Method: We reviewed 72 hippocampus specimens from January 1997 to July 2000. Student's t test for independent, samples, ANOVA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
4

Year Published

2005
2005
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 14 publications
0
7
0
4
Order By: Relevance
“…Presence of polyglucosans in neurons per se is possibly not the main factor leading to epilepsy, as neuronal PGBs are also found in patients with glycogen branching enzyme deficiency (glycogen storage disease type IV), which suffer from motor, sensory and autonomic deficits but not epilepsy (Robitaille et al, 1980). Inclusions of polyglucosans, named corpora amylacea in some old and new studies (for details on the nomenclature, see Cavanagh, 1999), have been frequently observed in cerebral astrocytes of patients suffering of several epileptic disorders and often correlated with seizure duration (Abel et al, 2010; Agari et al, 2012; Cherian et al, 2003; Chung and Horoupian, 1996; Das et al, 2011; Erdamar et al, 2000; Kakita et al, 2005; Kawamura et al, 2002; Nishio et al, 2001; Palmucci et al, 1982; Radhakrishnan et al, 2007; Radhakrishnan et al, 1999; Ribeiro Mde et al, 2003; Van Paesschen et al, 1997; Vanderhaeghen, 1971), although their occurrence has also been reported in various brain regions and even in other tissues either in the presence or in the absence of specific pathology (see Leel-Ossy, 1998). The aggregation of glycogen-like polymers is a complex and relatively unexplored phenomenon, which includes abnormal polyglucosans but also membrane-bound aggregates of normal β-glycogen (glycogenosomes) observed under various conditions such as lysosomal disorders and aging (Cavanagh and Jones, 2000).…”
Section: Synthesis Of Unmetabolizable Glycogen Is Correlated With Epimentioning
confidence: 99%
“…Presence of polyglucosans in neurons per se is possibly not the main factor leading to epilepsy, as neuronal PGBs are also found in patients with glycogen branching enzyme deficiency (glycogen storage disease type IV), which suffer from motor, sensory and autonomic deficits but not epilepsy (Robitaille et al, 1980). Inclusions of polyglucosans, named corpora amylacea in some old and new studies (for details on the nomenclature, see Cavanagh, 1999), have been frequently observed in cerebral astrocytes of patients suffering of several epileptic disorders and often correlated with seizure duration (Abel et al, 2010; Agari et al, 2012; Cherian et al, 2003; Chung and Horoupian, 1996; Das et al, 2011; Erdamar et al, 2000; Kakita et al, 2005; Kawamura et al, 2002; Nishio et al, 2001; Palmucci et al, 1982; Radhakrishnan et al, 2007; Radhakrishnan et al, 1999; Ribeiro Mde et al, 2003; Van Paesschen et al, 1997; Vanderhaeghen, 1971), although their occurrence has also been reported in various brain regions and even in other tissues either in the presence or in the absence of specific pathology (see Leel-Ossy, 1998). The aggregation of glycogen-like polymers is a complex and relatively unexplored phenomenon, which includes abnormal polyglucosans but also membrane-bound aggregates of normal β-glycogen (glycogenosomes) observed under various conditions such as lysosomal disorders and aging (Cavanagh and Jones, 2000).…”
Section: Synthesis Of Unmetabolizable Glycogen Is Correlated With Epimentioning
confidence: 99%
“…En estudios previos 10,11,17 o series de pacientes 8,9,15,18,19,[21][22][23][24][25][26] han descrito la acumulación abundante de CoA en la neocorteza y en el hipocampo de pacientes con ELTFR y EH. En los hipocampos resecados, los CoA han sido observados en las siguientes áreas: CA1, CA3 y CA4, folium terminal y fascia dentada, y en menor grado en la corteza parahipocampal 8,15,25 .…”
Section: Discussionunclassified
“…Los grupos de Ribeiro et al y Abubakr et al comentan una asociación entre la duración de la epilepsia y la presencia de CoA, pero localizados en el hipocampo, sugiriendo que la formación de CoA se debe al proceso epileptogénico 22,23 . Otros autores consideran que la formación de los CoA está relacionada con los procesos celulares inducidos por un daño 27 , entonces las crisis pudieran contribuir también a su desarrollo, localizados estos en el hipocampo o en la neocorteza.…”
Section: Discussionunclassified
“…No significant differences were evident between the two groups in age of seizure onset, duration of seizure or surgical outcome. However Ribeiro et al 17 reviewed 72 hippocampus specimens with the features of MTS and corpora amylacea (PGBs) was found in 35 patients (49%). Apart from prolonged epilepsy duration (mean 28.7 years) in the group of patients with corpora amylacea (PGBs) there are no significant differences in other risk factors or clinical features.…”
Section: Discussionmentioning
confidence: 99%